Microfluidic Rapid Prototype Enzymatic Biofuel Cell Based on a Nanocomposite - Mashayekhi Mazar, Fariba; Alijanianzadeh, Mahdi; Molaei Rad, Ahmad; Heydari, Payam (Frontiers in Mechanical Engineering, 2021)
Here, a low-cost glucose/O2 Y-shaped microfluidic biofuel cell was developed using a printed circuit board (PCB) for microelectrode construction. A double-side tape based on the pressure-sensitive adhesive (PSA) was used for microchannel fabrication. A nanocomposite consists of reduced graphene oxide (RGO), gold nanoparticles (AuNPs), and poly neutral red (PNR) connect to enzymes was applied on the copper electrode surface. The Aspergillus niger glucose oxidase enzyme and Mytheliophthora thermophile laccase were used to prepare the modified anodic and cathodic electrodes. Different procedures such as cyclic voltammetry (CV), scanning electron microscope (SEM) coupled with energy-dispersive x-ray spectroscopy (EDX), and atomic force microscopy (AFM) were scanned the modified electrodes. SEM/EDX microanalysis was showed the structural and morphological properties of the proposed nanocomposite. The biofuel cell performance was demonstrated the maximum power density of 36 μW cm−2, an open-circuit voltage (OCV) of 0.5 V with a flow rate of 50 L min-1. The proposed rapid technique with RGO/AuNPs/PNR bioelectrodes is a good approach for finding low-cost microfluidic biofuel cell.